Biochar has little effect on soil dissolved organic carbon pool 5 years after biochar application under field condition. (30th April 2019) - Dong, Xinliang; Singh, Bhupinder Pal; Li, Guitong; Lin, Qimei; Zhao, Xiaorong
Abstract: Biochar application can improve soil properties, such as increasing soil organic carbon content, soil pH and water content. These properties are important to soil dissolved organic carbon (DOC); however, the effects of biochar on DOC concentration and composition have received little research attention, especially several years after biochar application under field conditions. This study was conducted in a long‐term experimental field where the biochar was only applied once in 2009. The purpose of the study was to investigate the effect of different biochar application rates (0, 30, 60 and 90 t ha −1 ) on the dynamics of soil water content, DOC concentration and DOC compositions (reducing sugar, soluble phenol and aromatics) over nine samplings during a 12‐month period in 2014. Our results showed that soil water content and DOC concentration varied from 7.1% to 14.5% and 59 to 230 mg C kg −1 soil during the 12 months, respectively. However, the biochar application rates did not significantly ( p > 0.05) affect soil water content, DOC concentration and DOC composition at the same sampling period. The DOC concentration across the biochar treatments was positively correlated to soil water content. Moreover, the DOC composition (reducing sugar, soluble phenol or aromatics) and their concentrations were positively correlated to the total DOC concentration. In addition, biochar did not affect soil bulk density, pH, saturated hydraulic conductivity and crop yields. The results indicated that some benefits of biochar to soil may not persist 5 years after the application of biochar under a field condition.